The Influence of Brand Image, Product Quality, and Price on Interest in Buying Products: Case study at Ms Glow Beauty Store, Bukittinggi - Putri Dewi Mutia; Khadijah Nurani (Universitas Mercu Buana, 2023)
This study intends to analyze the impact of price, customer desire, and product quality on customer satisfaction. This is a quantitative research with causality. The sampling technique used is purposive sampling, the information used is basic information obtained from the owner of Sanjai Sil, Aur Kuning Bukittinggi. The information analysis method used is Multiple Linear Regression, data analysis using SPSS 16. The results of this study found that the three exogenous variables of customer desire, product quality and price have a positive effect on customer satisfaction which encourages interest in buying the product.